Membrane microdomains in immunoreceptor signaling - Horejsi, Vaclav; Hrdinka, Matous (FEBS letters, 2014)
Membrane microdomains denoted commonly as lipid rafts (or membrane rafts) have been implicated in T-cell receptor (TCR), and more generally immunoreceptor, signaling for over 25 years. However, this area of research has been complicated by doubts about the real nature (and even existence) of these membrane entities, especially because of methodological problems connected with possible detergent artefacts. Recent progress in biophysical approaches and functional studies of raft resident proteins apparently clarified many controversial aspects in this area. At present, the prevailing view is that these membrane microdomains are indeed involved in many aspects of cell biology, including immunoreceptor signaling. Moreover, several other types of raft-like microdomains (perhaps better termed nanodomains) have been described, which apparently also play important biological roles.
Keywords: Receptors, Antigen, T-Cell; signální transdukce; Signal Transduction; receptory antigenů T-buněk; Immunoreceptor signaling; zvířata; Humans; membránové mikrodomény; Lipid raft; Membrane Microdomains; lidé; Leukocyte; Animals